Effects of Brief Messaging About Undiagnosed Infections Detected through HIV Testing Among Black and Latino Men Who Have Sex With Men in the United States. Issue 12 (December 2015) - Mansergh, Gordon; Miller, Paige; Herbst, Jeffrey H.; Mimiaga, Matthew J.; Holman, Jeremy
Abstract : Abstract: We examined intent to get tested for HIV infection and use condoms among n = 604 uninfected black and Latino men who have sex with men after receiving brief information messaging that 1 in 10 minority men who have sex with men had HIV infection and did not know it. Information awareness, newness, believability, HIV testing cost willingness, and associated demographic variables were also assessed. Abstract : US black and Latino men who have sex with men were presented with a brief message about study findings of undiagnosed HIV infections, and then assessed for intent to get an HIV test and use condoms.